Surgical Excision of an Adrenal Neuroblastoma in a Dog - Mestrinho, Lisa Alexandra; Marques, Maria Inês; Jesus, Sandra; Pissarra, Hugo; Peleteiro, Maria; Ferreira, Antonio (Frontiers in Veterinary Science, 2019)
A 11-month-old, intact male, Rhodesian Ridgeback was presented to the Veterinary Teaching Hospital with signs of inappetence, lethargy, and abdominal pain for 3 days. A large and well-defined abdominal retroperitoneal mass, related with the left kidney, at the expected location of the adrenal gland, was revealed by radiography, ultrasound, and computed tomography. The mass extended caudally to the iliac artery bifurcation, compressing the aorta, caudal vena cava, and both kidneys. Cytology findings were compatible with a malignant round cell tumor. The most probable diagnosis was neuroblastoma. Following a comprehensive discussion with the owners about a treatment plan, surgical excision was performed. Because a wide excision would compromise major vessels, excision was performed after careful dissection of the aorta and vena cava. The left kidney was removed because the proximal ureter could not be separated from the tumor. The animal recovered successfully. Diagnosis was confirmed by histopathology and immunohistochemistry, but the owners decided not to pursue any further treatment. Clinical signs of abdominal pain recurred within 1 month following surgery. Therefore, the animal was euthanized upon the owners’ request. This report describes the diagnosis, surgical treatment, and follow-up of a dog with an abdominal peripheral neuroblastoma.